The effectiveness of corticosteroid injection versus night splints for carpal tunnel syndrome: 24-month follow-up of a randomized trial. (8th April 2022) - Burton, Claire; Rathod-Mistry, Trishna; Blackburn, Steven; Blagojevic-Bucknall, Milica; Chesterton, Linda; Davenport, Graham; Dziedzic, Krysia; Higginbottom, Adele; Jowett, Sue; Myers, Helen; Oppong, Raymond; van der Windt, Danielle; et al.
Abstract: Objectives: This follow-up study of the INSTinCTS (INjection vs SplinTing in Carpal Tunnel Syndrome) trial compared the effects of corticosteroid injection (CSI) and night splinting (NS) for the initial management of mild-to-moderate CTS on symptoms, resource use and carpal tunnel surgery, over 24 months. Methods: Adults with mild-to-moderate CTS were randomized 1:1 to a local corticosteroid injection or a night splint worn for 6 weeks. Outcomes at 12 and 24 months included the Boston Carpal Tunnel Questionnaire (BCTQ), hand/wrist pain intensity numeric rating scale (NRS), the number of patients referred for and undergoing CTS surgery, and healthcare utilization. A cost–utility analysis was conducted. Results: One hundred and sixteen participants received a CSI and 118 a NS. The response rate at 24 months was 73% in the CSI arm and 71% in the NS arm. By 24 months, a greater proportion of the CSI group had been referred for (28% vs 20%) and undergone (22% vs 16%) CTS surgery compared with the NS group. There were no statistically significant between-group differences in BCTQ score or pain NRS at 12 or 24 months. CSI was more costly [mean difference £68.59 (95% CI: −120.84, 291.24)] with fewer quality-adjusted life-years than NS over 24 months [mean difference −0.022 (95% CI: −0.093, 0.045)]. Conclusion: Over 24 months, surgical intervention rates were low in both groups, but less frequent in the NS group. While there were no differences in the clinical effectiveness of CSI and NS, initial treatment with CSI may not be cost-effective in the long-term compared with NS.